2021
DOI: 10.1093/neuonc/noab195.008
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal changes in along-tract profilometry of cerebellar peduncles in cerebellar mutism syndrome

Abstract: Aims Cerebellar mutism syndrome occurs in 25% of children following resection of posterior fossa tumours. Characterised by mutism, emotional lability and cerebellar motor signs, the syndrome is usually reversible over weeks to months. Its pathophysiology remains unclear, but evidence from diffusion MRI studies has implicated damage to the superior cerebellar peduncles in the development of this condition. The objective of this study was to describe the application of automated tractography of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
2
1
Order By: Relevance
“…Here we further found that the right superior cerebellar peduncle was especially involved in CMS as more massive voxels localized in the right side. However, this is inconsistent with another study, which indicated that the left superior cerebellar peduncle was associated with CMS ( Toescu et al, 2022 ). The laterality of superior cerebellar peduncles associated with CMS still needs to be studied further.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…Here we further found that the right superior cerebellar peduncle was especially involved in CMS as more massive voxels localized in the right side. However, this is inconsistent with another study, which indicated that the left superior cerebellar peduncle was associated with CMS ( Toescu et al, 2022 ). The laterality of superior cerebellar peduncles associated with CMS still needs to be studied further.…”
Section: Discussioncontrasting
confidence: 78%
“…Controversy remains regarding the laterality of superior cerebellar peduncle (SCP) damage in CMS occurrence. Previous diffusion-weighted studies have detected significant fractional anisotropy (FA) reduction in bilateral superior peduncles in CMS cases compared with non-CMS cases ( Albazron et al, 2019 , Avula et al, 2015 , McEvoy et al, 2016 , Morris et al, 2009 ), while others found only unilateral (right or left) impairment in SCP is associated with CMS ( Law et al, 2012 , Toescu et al, 2022 , Vedantam et al, 2019 ), with fiber pathway damage lasting for a long time ( McEvoy et al, 2016 ). Besides, no difference was detected in MCP bilaterally or unilaterally ( Vedantam et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8] This constellation of symptoms is commonly referred to as cerebellar mutism syndrome (CMS), 9 posterior fossa syndrome, or cerebellar cognitive affective syndrome +/-cerebellar mutism; we will use the term CMS for this paper. The duration and severity of this syndrome is variable, but importantly, patients who develop CMS typically have worse long-term cognitive outcomes, 5,[10][11][12][13] highlighting the importance of this syndrome as a potential harbinger of long-term impairment.…”
Section: Introductionmentioning
confidence: 99%